A commutation failure risk analysis method considering the interaction of inverter stations. (September 2020) - Yang, Weichen; Miao, Shihong; Zhang, Shixu; Li, Yaowang; Han, Ji; Xu, Hanping; Zhang, Dongyin
Highlights: Different types of commutation failure are revealed and analyzed. The interaction mechanism of multi-infeed HVDC system is analyzed. A novel method is developed to assess the commutation failure risk. Abstract: In the multi-infeed HVDC system, the interaction between inverter stations is an important factor that triggers the propagation of commutation failure. This paper aims to study the interaction mechanism of inverter stations and propose a reasonable method to evaluate the commutation failure risk. Firstly, based on the modified switching function, the commutation failure component is formulated to describe the commutation process and transient characteristics of inverter station during the commutation failure. Then, the analytical calculation method is studied to reflect the commutation voltage fluctuation under the influence of AC fault and commutation failure. On this basis, the commutation failure risk is assessed by comparing each valve's maximum commutation area with the minimum commutation area required for blocking. By analyzing the commutation failure risk under different grounding impedances, it is possible to identify the critical grounding inductance that causes a remote commutation failure. Based on the multi-infeed HVDC system in PSCAD/EMTDC, the validity and accuracy of the proposed method and commutation failure component are verified.